2022
DOI: 10.7759/cureus.30831
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Catheter Migration: A Case Report of a CT Scan Examination

Abstract: Epidural catheter placement is one of the most effective, secure, and worldwide used pain control modalities. Epidural catheter dislodgment is a common cause of epidural block failure. The diagnosis of this situation is usually presumptive, and cases in which the actual trajectory and final location of the catheter are witnessed by imaging are rare.We present two cases of the insufficient epidural block due to catheter migration, confirmed by a CT scan with radiopaque contrast injection through the catheter. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous methods of confirming epidural catheter placement have been reported including but not limited to electrical stimulation as described by Tsui et al [ 11 ], interpretation of epidural pressure waveforms as described by Ghia et al [ 12 ], CT epidurography [ 13 ], contrast injection, and X-ray confirmation. These methods are technically difficult and require special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous methods of confirming epidural catheter placement have been reported including but not limited to electrical stimulation as described by Tsui et al [ 11 ], interpretation of epidural pressure waveforms as described by Ghia et al [ 12 ], CT epidurography [ 13 ], contrast injection, and X-ray confirmation. These methods are technically difficult and require special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmation is only possible however in patients who have received an epidural rather than an epidural as part of a CSE or if a general anaesthetic is administered before the development of sensory loss. Despite several advancements in epidural catheter material and tip designs, malpositioned epidural catheters continue to occur [1][2][3]. It is reported that 27% of lumbar epidurals fail but, in many cases, the underlying cause for the failure is undetermined [4].…”
mentioning
confidence: 99%